Draft Assembly of Elite Inbred Line PH207 Provides Insights into Genomic and Transcriptome Diversity in Maize. Issue 11 (1st November 2016) - Hirsch, Candice N.; Hirsch, Cory D.; Brohammer, Alex B.; Bowman, Megan J.; Soifer, Ilya; Barad, Omer; Shem-Tov, Doron; Baruch, Kobi; Lu, Fei; Hernandez, Alvaro G.; Fields, Christopher J.; Wright, Chris L.; et al.
Abstract : Comparative analyses of the maize reference B73 genome assembly and the newly assembled PH207 genome and their transcriptomes provide insights into variation between heterotic groups of elite maize. Abstract: Intense artificial selection over the last 100 years has produced elite maize ( Zea mays ) inbred lines that combine to produce high-yielding hybrids. To further our understanding of how genome and transcriptome variation contribute to the production of high-yielding hybrids, we generated a draft genome assembly of the inbred line PH207 to complement and compare with the existing B73 reference sequence. B73 is a founder of the Stiff Stalk germplasm pool, while PH207 is a founder of Iodent germplasm, both of which have contributed substantially to the production of temperate commercial maize and are combined to make heterotic hybrids. Comparison of these two assemblies revealed over 2500 genes present in only one of the two genotypes and 136 gene families that have undergone extensive expansion or contraction. Transcriptome profiling revealed extensive expression variation, with as many as 10, 564 differentially expressed transcripts and 7128 transcripts expressed in only one of the two genotypes in a single tissue. Genotype-specific genes were more likely to have tissue/condition-specific expression and lower transcript abundance. The availability of a high-quality genome assembly for the elite maize inbred PH207 expands our knowledge of the breadth of natural genome and transcriptome variation in elite maize inbred lines across heterotic pools.